1978
DOI: 10.1136/bmj.1.6108.270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of induced abortion on gestational duration in subsequent pregnancies.

Abstract: made at random, which gives a good indication of the mean COHb concentration in smokers.7A history of an attack of chest pain suggesting myocardial infarction was associated with raised COHb concentrations; a similar relation was not found for smoking history. The association was unlikely to have been caused by greater frequency of "false" attacks of chest pain in men with raised COHb concentrations because. a similar association was found for ECG signs of myocardial infarction. The association was mainly caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 5 publications
(1 reference statement)
0
5
0
1
Order By: Relevance
“…We found 24 studies that explored associations between abortion and PTB (or a surrogate marker For PTB - low birth weight [LBW]) (Appendix-Table 4). 4972 Twelve studies found an association between these two phenomena with consistent results in risk ratio elevation of 1.3–2.0. Moreover, seven of the twelve identified a “dose response effect” with risk estimates rising as a woman had more induced abortions.…”
Section: Induced Abortion and Subsequent Preterm Birth (Ptb)mentioning
confidence: 61%
“…We found 24 studies that explored associations between abortion and PTB (or a surrogate marker For PTB - low birth weight [LBW]) (Appendix-Table 4). 4972 Twelve studies found an association between these two phenomena with consistent results in risk ratio elevation of 1.3–2.0. Moreover, seven of the twelve identified a “dose response effect” with risk estimates rising as a woman had more induced abortions.…”
Section: Induced Abortion and Subsequent Preterm Birth (Ptb)mentioning
confidence: 61%
“…The results of the search, the study selection log and the number of studies are reported (Figure 1). Thirty‐seven studies were included in this review 4,10–45 . Thirty‐two studies were excluded: Seven studies 3,46–51 reported no neonatal outcome, seven studies 52–58 reported combined spontaneous and I‐TOP data, five studies 59–63 had no comparator group, four reports 5,64–66 were reviews, three studies 67–69 reported on very preterm and moderately preterm data only, two studies 70,71 reported on specific population only, two studies 72,73 had already included data from other reports, one report 74 was a duplicate publication and for one study, 75 data were not ascertainable.…”
Section: Resultsmentioning
confidence: 99%
“…Reports in the early 1970's suggesting considerably increased risks of preterm deliveries and low birthweight infants in pregnancies after induced abortion (2, 6, 14, 27) have caused major concern. Knowledge acquired from studies performed during the 1970's, however, have indicated either no or only a slightly increased risk of an unfavorable outcome of subsequent pregnancy after an early induced abortion (3,4,11,29,30,32). but the findings are still conflicting.…”
mentioning
confidence: 99%